Estimated incidence of disruptions to event-free survival from non-metastatic cancers in New South Wales, Australia - a population-wide epidemiological study of linked cancer registry and treatment data - Morrell, Stephen; Roder, David; Currow, David; Engel, Alexander; Hovey, Elizabeth; Lewis, Craig R.; Liauw, Winston; Martin, Jarad M.; Patel, Manish; Thompson, Stephen R.; O’Brien, Tracey (Frontiers in Oncology, 2024)
Population cancer registries record primary cancer incidence, mortality and survival for whole populations, but not more timely outcomes such as cancer recurrence, secondary cancers or other complications that disrupt event-free survival. Nonetheless, indirect evidence may be inferred from treatment data to provide evidence of recurrence and like events, which can facilitate earlier assessment of care outcomes.The present study aims to infer such evidence by applying algorithms to linked cancer registry and treatment data obtained from hospitals and universal health insurance claims applicable to the New South Wales (NSW) population of Australia.Primary invasive cancers from the NSW Cancer Registry (NSWCR), diagnosed in 2001-2018 with localized or regionalized summary stage, were linked to treatment data for five common Australian cancers: breast, colon/rectum, lung, prostate, and skin (melanomas). Clinicians specializing in each cancer type provided guidance on expected treatment pathways and departures to indicate remission and subsequent recurrence or other disruptive events.A sample survey of patients and clinicians served to test initial population-wide results. Following consequent refinement of the algorithms, estimates of recurrence and like events were generated. Their plausibility was assessed by their correspondence with expected outcomes by tumour type and summary stage at diagnosis and by their associations with cancer survival.Kaplan-Meier product limit estimates indicated that 5-year cumulative probabilities of recurrence and other disruptive events were lower, and median times to these events longer, for those staged as localized rather than regionalized. For localized and regionalized cancers respectively, these were: breast -7% (866 days) and 34% (570 days); colon/rectum -15% (732 days) and 25% (641 days); lung -46% (552 days) and 66% (404 days); melanoma -11% (893 days) and 38% (611 days); and prostate -14% (742 days) and 39% (478 days). Cases with markers for these events had poorer longer-term survival.These population-wide estimates of recurrence and like events are approximations only. Absent more direct measures, they nonetheless may inform service planning by indicating population or treatment sub-groups at increased risk of recurrence and like events sooner than waiting for deaths to occur.